Generation and characterization of novel transcriptome-derived SSR markers for genetic applications in blueberry - Krishnanand P. Kulkarni; Richmond K. Appiah; Jennifer Johnson-Cicalese; Nicholi Vorsa; Umesh K. Reddy; Sathya Elavarthi; Hamed Bostan; Massimo Iorizzo; Kalpalatha Melmaiee (Scientific Reports)
Abstract Blueberries (Vaccinium spp.) are small fruit crops native to North America but grown commercially in several countries. There has been a steady increase in consumer demand for blueberries, owing to their numerous health benefits attributable to the high content of antioxidant compounds. Despite its importance, limited genomic resources are available, hindering genetic research and improvement in blueberry. In this study, we developed novel transcriptome-derived simple sequence repeat (SSR) markers from two divergent blueberry species. We identified 64,013 SSRs from 208,286 unigenes de novo assembled from 135 million high-quality sequence reads. SSRs with mononucleotide repeat motifs were most abundant, followed by di-, tri-, tetra-, penta-, and hexanucleotide repeat motifs. The repeat motif AG/CT was most abundant (84%) compared to the other three dinucleotide repeat motifs, AC/TG, AT/TA, and CG/GC. Similarly, AAG/CTT and AAAT/ATTT were the most abundant tri- and tetra-nucleotide repeat motifs, respectively. We designed 33,179 primer pairs from 64,013 SSR motifs. Genomic coordinates of these primers were identified using a chromosome-scale reference genome sequence of diploid blueberry clone W85-20. After discarding those markers mapped with MapQ < 1, genomic positions for 19,310 markers were identified. Thirty-six SSRs differing in nucleotide repeat motifs were randomly selected for PCR optimization, characterization, and amplification in 45 diverse Vaccinium species. Thirty-four primers generated 158 alleles with an average of 4.6 alleles per locus. Genetic structure analyses revealed a high genetic differentiation among the selected species, and divided 45 accessions into two to five clusters. Furthermore, the selected SSR markers showed 88.2–97% cross-species transferability, suggesting the possibility of using these markers for various genetics and comparative genomics applications in blueberry and cranberry species. Thus, the transcriptome-derived SSR markers developed in this study could serve as a valuable resource for further genetic and evolutionary studies in Vaccinium species.